A review on touch DNA collection, extraction, amplification, analysis and determination of phenotype. (July 2022) - Nimbkar, Pratiksha H.; D. Bhatt, Vaibhav
Abstract: DNA is used as confirmatory evidence in criminal investigations for a long time. With advancements in DNA collection and analysis, investigators can analyse samples collected at nanogram levels. For decades now, touch DNA has been used for comparison and individualization as it has a greater probability of being present at a crime scene. With the advancements in sciences, today there are methods available for the determination of phenotype for DNA sequences through analysis of Single Nucleotide Polymorphisms (SNPs). A freely available and forensically validated web software is HIrisPlex-S developed by the Erasmus Medical Centre, Netherlands in collaboration with the Walsh Laboratory of Indiana-University-Purdue-University-Indianapolis (IUPUI), USA. It can expand the horizons in forensic science enabling investigators to get an idea of the phenotype of a suspected perpetrator and thereby reduce the suspect list to a great extent. There are numerous methods enlisted for the collection and processing of touch DNA. The review paper attempts to compile the various methods adopted in touch DNA collection and analysis as well as the related literature on phenotyping using the HIrisPlex-S Software. Highlights: Touch DNA in Forensic Investigations. Methods of Touch DNA collection and Analysis Determination of Phenotype. Forensically Validated Web Software - HIrisPlex-S.